Specificity in English for Academic Purposes (EAP): a corpus analysis of lexical bundles in academic writing - Ang, Leng Hong; Tan, Kim Hua (Penerbit Universiti Kebangsaan Malaysia, 2018)
The issue of specificity in English for Academic Purposes (EAP) settings has always challenged linguists and instructors in the field to take a stance on how language should be perceived, that is whether language forms and features are transferable across different academic disciplines or are specific to particular disciplines. This study intends to take this debate a step further by employing a corpus-driven method in identifying a type of phraseological sequence, namely lexical bundles in a corpus of journal articles in the field of International Business Management (IBM). The lexical bundles were compared with those compiled by Simpson-Vlach and Ellis (2010) in their study of Academic Formulas List (AFL) to determine the specificity of the lexical bundles identified in this study. Following frequency-based approach, the corpus tool, Collocate 1.0 was used to extract three- to five-word sequences. These word sequences were manually filtered to exclude irrelevant and meaningless combinations. The qualified lexical bundles were compiled and compared with lexical bundles in AFL (Simpson-Vlach and Ellis 2010) using log-likelihood test. The findings show that three-word lexical bundles are the most common types of lexical bundles in IBM corpus. The comparison reveals that lexical bundles in IBM corpus are relatively specific as compared with lexical bundles in AFL. A discipline-specific approach to the teaching and learning of lexical bundles in EAP settings is therefore advocated to enhance EAP syllabuses and instruction.